Treatment of severe actinic rectitis - Rossi, Benedito Mauro; Nakagawa, Wilson Toshihiko; Fernandes, José Augusto P.; Lopes, Ademar; Paegle, Lauma Dzidra (São Paulo Medical Journal, 1998)
BACKGROUND: The authors report the treatment of three female patients with severe actinic rectitis, with stenosis or perforation, submitted to anterior proctosigmoidectomy and transanal coloanal anastomosis. METHODS: In all cases surgery consisted of total proctosigmoidectomy, mucosectomy of the anal canal, lowering of the left colon through the pelvis and transanal anastomosis performed manually at the level of the pectineal line using separate absorbable sutures. A protective intestinal shunt was performed in all cases. RESULTS: The three patients did not present transoperative or immediate postoperative complications, but the first patient developed deep venous thrombosis of the leg that was submitted to successful clinical treatment. The intestinal shunts were later closed in all three cases. Sphincter function was considered very good in the first case and regular in the remaining two. CONCLUSION: The surgical technique utilized was considered to be adequate for the cases reported and is the first option for the maintenance of transit in patients with severe actinic rectitis since the anastomosis is performed using non-irradiated colon with the pectineal line, practically outside the pelvis.